Nickel electrodes as a cheap and versatile platform for studying structure and function of immobilized redox proteins - Han, Xiao Xia; Li, Junbo; Oener, Ibrahim Halil; Zhao, Bing; Leimkuehler, Silke; Hildebrandt, Peter; Weidinger, Inez M. (Analytica Chimica Acta, 2016)
Practical use of many bioelectronic and bioanalytical devices is limited by the need of expensive materials and time consuming fabrication. Here we demonstrate the use of nickel electrodes as a simple and cheap solid support material for bioelectronic applications. The naturally nanostructured electrodes showed a surprisingly high electromagnetic surface enhancement upon light illumination such that immobilization and electron transfer reactions of the model redox proteins cytochrome b5 (Cyt b5) and cytochrome c (Cyt c) could be followed via surface enhanced resonance Raman spectroscopy. It could be shown that the nickel surface, when used as received, promotes a very efficient binding of the proteins upon preservation of their native structure. The immobilized redox proteins could efficiently exchange electrons with the electrode and could even act as an electron relay between the electrode and solubilized myoglobin. Our results open up new possibility for nickel electrodes as an exceptional good support for bioelectronic devices and biosensors on the one hand and for surface enhanced spectroscopic investigations on the other hand.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biocompatibility; Electron relay; Electron transfer; Ni electrodes; Redox proteins; Surface enhanced Raman spectroscopy